Adobe Animate 2022 for Creative Professionals - Second Edition - Labrecque, Joseph (Packt Publishing, 2022)
Step into the world of animation and go beyond the fundamentals of Adobe Animate to bring experiences to life with the help of expert-led content Key Features Produce rich motion graphics and interactive animations for multiple platforms Explore the key features and enhancements in the latest Adobe Animate release Take your Adobe Animate projects to the next level with creative workflows Book Description Adobe Animate is platform-agnostic asset creation, motion design, animation, and interactivity software. Complete with explanations of essential concepts and step-by-step walkthroughs of practical examples, this book will guide you in using Adobe Animate to create immersive experiences by breaking through creative limitations across every medium. We begin by getting up to speed with all that you need to know about Adobe Animate. You'll learn how to get started with Animate as a creative platform and explore the features introduced in its most recent versions. The book will show you how to consume and produce media assets for multiple platforms through both the publish and export workflows. Following this, you'll explore advanced rigging techniques and discover how to create more dynamic animation with advanced depth and movement techniques. You'll also find out how to build projects such as games, virtual reality experiences, and apps for various platforms as the book demonstrates different ways to use Animate. Finally, it covers the different methods used to extend the software for various needs. By the end of this Adobe Animate book, you'll be able to produce a variety of media assets, motion graphic design materials, animated artifacts, and interactive content pieces for platforms such as HTML5 Canvas, WebGL, and mobile devices. What you will learn Gain a solid understanding of Adobe Animate foundations and new features Understand the nuances associated with publishing and exporting rich media content to various platforms Make use of advanced layering and rigging techniques to create engaging motion content Create dynamic motion using the camera and variable layer depth techniques Develop web-based games, virtual reality experiences, and multiplatform mobile applications Extend Animate with extensions, application-level scripting, and the creation of custom integrated tutorials Who this book is for This book is for web, graphic, and motion design professionals with basic experience in animation who want to take their existing skills to the ...